(3eZfj GdWdGHs - (3GdeZfjSGhj, eMehO Hf MSf ` J (B1222 (3g`s ((3YejQ QTOj efdGs)
(3ChdgG (B:s
(3fMeOc jG ef LYd GdefWb ejRGfG dWQjb GdJagje adeG cGfJ GdQSGdI GdeTghQI HEjSGZhLj GdefShHI Edi GdTjN GdYdGeI CKjQ GdOjf GdCHgQj eMJhjI Ydi GdYLGFH ef GdbhGYO heTJedI Ydi GdZQGFH ef GdahGFO s
(3BNQgG (B:s
(3eYJeOG aj GdOYhI Edi SHjd GdMb dcf HGdfSHI Edi faS GdeSJOd GdYeOI gh GdHQgGf abO EP Hg jJhUd Edi JMbjb GdMbGFb hJObjb GdObjb hHg jJhSd Edi EOQGc GdUhQ GdbOSjI hGdCMcGe GdfHhjI hdPgG NU GdeUfa GdYeOI HGdHQgGf abW JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7/167s
(3EjVGM Gdecfhf (B1/153s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs